Synthesis, Structure, and Magnetic Properties of Phosphinate‐Bridged Hexanuclear FeIII Complexes Containing Two Butterfly‐Shaped Fe3O Cores. Issue 34 (3rd November 2015) - Goura, Joydeb; Oyarzabal, Itziar; Colacio, Enrique; Chandrasekhar, Vadapalli
Abstract: The reaction of Fe III salts with 1, 1, 2, 3, 3‐pentamethyltrimethylenephosphinic acid [ cyc PO2 H] or dicyclohexylphosphinic acid [(C6 H11 )2 PO2 H] along with pivalic acid in the presence of triethylamine leads to the formation of two hexanuclear iron(III) clusters: [Fe III 6 (μ3 ‐O)2 (μ‐OH)2 (μ ‐cyc PO2 )6 (μ‐ t BuCO2 )6 (η 1 ‐ t BuCO2 H)2 ]· 4CH3 CN· 3CH2 Cl2 (1 ) and [Fe III 6 (μ3 ‐O)2 (μ‐OH)2 μ‐(C6 H11 )2 PO2 6 (μ‐ t BuCO2 )6 (η 1 ‐OH2 )2 ]· 2CH3 CN· CH2 Cl2 (2 ). These complexes are made up of two butterfly‐shaped Fe III 3 O subunits that are joined to each other by two bridging phosphinate ligands. In addition, the formation of1 and2 is assisted by μ3 ‐O, μ‐OH, and pivalate ligands. Variable‐temperature magnetic susceptibility measurements of complexes1 and2 reveal medium to strong antiferromagnetic interactions between the Fe III ions inside the Fe3 O subunits and weak inter‐trinuclear antiferromagnetic interactions through the bridging phosphinate ligands. The triangular topology of the Fe3 O subunits gives rise to competing antiferromagnetic interactions and spin frustration. The different relative magnitudes of the competing interactions leads to S = 5/2 and S = 1/2 ground spin states for the Fe3 O subunits in1 and2, respectively. Abstract : The multicomponent reaction of Fe III salts with 1, 1, 2, 3, 3‐pentamethyltrimethylenephosphinic acid or (C6 H11 )2 PO2 H with pivalic acid and triethylamine base afforded a dimeric ensemble of Fe3 O core, hexanuclear iron(III) phosphinate clusters. The complexes are made up of two butterfly‐shaped Fe III 3 –O subunits joined by two bridging phosphinate ligands. Magnetic studies on the complexes (1 and2 ) reveal the presence of weak antiferromagnetic coupling between the Fe III ions.